2019
DOI: 10.1186/s12893-019-0611-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopically excised retroperitoneal presacral Schwannoma: atypical pre and postoperative manifestations – case report

Abstract: BackgroundWe are a reporting a rare case of retroperitoneal schwanomma with atypical pre and postoperative manifestations. Retroperitoneal schwannomas are rare tumors that are difficult to preoperatively diagnose.Case presentationThis is a case report of a male patient, 41 years old, with symptoms of hipogastric and lower right member pain, as well as a history of a papilliferous thyroid tumor. Computerized tomography exams were inconclusive, showing a mass in the presacral region with dimensions of 4.4 × 3.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The most commonly observed complication is recurrence (5–10%) [6] . Only two other studies [7] , [8] , other than ours, indicated postoperative autonomic nerve system dysfunction due to Nervi Erigentes' manipulation. The Nervi Erigentes are splanchnic nerves that arise from sacral spinal nerves that migrate through the hypogastric plexus along the cavernous nerves, providing parasympathetic innervation to erectile bodies [9] .…”
Section: Discussionmentioning
confidence: 49%
“…The most commonly observed complication is recurrence (5–10%) [6] . Only two other studies [7] , [8] , other than ours, indicated postoperative autonomic nerve system dysfunction due to Nervi Erigentes' manipulation. The Nervi Erigentes are splanchnic nerves that arise from sacral spinal nerves that migrate through the hypogastric plexus along the cavernous nerves, providing parasympathetic innervation to erectile bodies [9] .…”
Section: Discussionmentioning
confidence: 49%
“…1 It usually occurs in the cephalocervical region and limbs but is rare in the presacral region. 2,3 Schwannoma is a benign tumor that can cause intense FDG uptake. 4 The quinoline-based imaging agent tracer FAPI can be used to detect a variety of cancers.…”
mentioning
confidence: 99%
“…Schwannoma is a benign tumor that develops in the Schwann cells of nerve fibers 1. It usually occurs in the cephalocervical region and limbs but is rare in the presacral region 2,3. Schwannoma is a benign tumor that can cause intense FDG uptake 4.…”
mentioning
confidence: 99%